GAME EDUCATION: MEDIA PEMBELAJARAN UNTUK MATERI BERPIKIR KOMPUTASIONAL SISWA SMP - Indah Febrianur; Mutiara Felicita Amsal; Rosmaria; Elsa Masriani (STKIP Subang, 2026)
This study aims to develop a game-based learning media for computational thinking material for seventh-grade junior high school students. This development is motivated by the limited use of interactive learning media, which has resulted in low student motivation and understanding. Therefore, an innovative learning medium is needed to create a more engaging and enjoyable learning environment. This study employed the 4D development model, consisting of the define, design, develop, and disseminate stages. The subjects of this study were seventh-grade students. The instruments used in this research included expert validation questionnaires and practicality questionnaires to evaluate the feasibility and usability of the developed media. The results indicate that the developed game-based learning media is categorized as very valid, with media validation scores of 4.60 and 4.53, and a material validation score of 4.84. In addition, the practicality test result obtained a score of 4.54, which falls into the very practical category. The media is equipped with learning materials, introductory games, and interactive evaluations that facilitate students in understanding the concepts of decomposition and pattern recognition. Therefore, the developed media can be used as an alternative learning medium that is engaging, interactive, and effective in improving students’ understanding of computational thinking material.